Comparison of brachial artery vasoreactivity in elite power athletes and age-matched controls - Welsch, M. A.; Blalock, P.; Credeur, D. P.; Parish, T. R. (PLOS ONE, 2013)
Elite endurance athletes typically have larger arteries contributing to greater skeletal muscle blood flow, oxygen and nutrient delivery and improved physical performance. Few studies have examined structural and functional properties of arteries in power athletes.